1997
DOI: 10.1542/peds.99.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders in Adult Patients With Early-treated Phenylketonuria

Abstract: Our results support a psychological perspective for the development of psychiatric symptoms in PKU. Thus, optimizing medical treatment necessary to prevent brain damage should be accompanied by psychiatric monitoring and psychological support for the families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 22 publications
4
85
0
5
Order By: Relevance
“…This does not encourage the removal of dietary treatment during adolescence, but it suggests relaxation of diet may not result in progression of neuropsychological deficits. Pietz et al (1997) suggested that adults with PKU may have an increased prevalence of psychiatric disorders despite continuing dietary treatment. When comparing 35 adults with PKU to a control group of 181 18-year-old subjects, 25.7 percent of those with PKU exhibited psychiatric disorders compared to 16.1 percent of controls.…”
Section: Processing Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not encourage the removal of dietary treatment during adolescence, but it suggests relaxation of diet may not result in progression of neuropsychological deficits. Pietz et al (1997) suggested that adults with PKU may have an increased prevalence of psychiatric disorders despite continuing dietary treatment. When comparing 35 adults with PKU to a control group of 181 18-year-old subjects, 25.7 percent of those with PKU exhibited psychiatric disorders compared to 16.1 percent of controls.…”
Section: Processing Speedmentioning
confidence: 99%
“…When comparing 35 adults with PKU to a control group of 181 18-year-old subjects, 25.7 percent of those with PKU exhibited psychiatric disorders compared to 16.1 percent of controls. The psychiatric symptoms included depressed mood, phobias, generalized anxiety, hypochondria worries, and anxiety at work (Pietz et al 1997). However, a study comparing women who were late-treated or off-diet with early-and continuously-treated women demonstrated significantly higher scores on measures of social introversion and psychopathology than the early-treated group (Brumm and Grant 2010).…”
Section: Processing Speedmentioning
confidence: 99%
“…As a consequence, eating disorders are not uncommon in PKU patients (Burgard et al, 1994;Pietz et al, 1997;Weglage et al, 2000;Anon, 2001). If dietary restrictions can be eased without compromising metabolic control, this can be expected to improve the quality of life and may even enhance compliance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggest that these controlled patients still suffer some cognitive loss and clear neurologic stress (Diamond et al, 1997;Levy, 1999;Pietz et al, 1997Pietz et al, ,1998Pietz, 1998). Thus while dietary therapy for PKU can alleviate many of the most deleterious effects of the disease, it is not completely successful from a clinical standpoint.…”
Section: Introductionmentioning
confidence: 99%